The Urgency of Digitalization Vis-a-Vis Business Trends (Indonesia Case) - Lucky Nugroho; Surender Mor; Diah Iskandar; Erna Setiany; Daru Asih; Febyola Mellin (IAEI, 2023)
The purpose of this conceptual paper is to understand how entrepreneurs cope with the challenges posed by Gen Z and Millennials consumers in the era of COVID-19, the era of Volatility, Uncertainty, Complexity, and Ambiguity (VUCA), the era of Industrial Revolution 4.0 and consumer retention under this uncertain business environment. We employed a descriptive-qualitative method to analyse Indonesia's Gen Z and Millennials. The findings infer that present-day entrepreneurs have swiftly adapted to the earlier challenges and successfully survived and competed with businesses. The study suggests that the needs and desires of Gen Z and Millennials, new normal conditions, the VUCA era, and the Industrial Revolution 4.0 emerged as crucial factors for entrepreneurs in adapting to the business in uncertain scenarios. The paper's inferences can be significant for entrepreneurs, businesses, and future researchers as it provides information, references, and scientific treasures for entrepreneurs, businesses, and consumers, especially Gen Z and Millennials.